The Role of Islamic Religious Education Teachers in the Development of Religious Characters in Limited Face-to-Face Learning at Senior High School - Rahma Septia Azizah; Isa Anshori (Adabiyah: Jurnal Pendidikan Islam, 2022)
This study aims to explore and understand the role of PAI teachers in fostering religious character during PTMT with a hybrid learning model at SMA Antartika Sidoarjo and to find out the supporting and inhibiting factors. The research method used is descriptive qualitative which produces data in the form of written words from the results of interviews, observations and documentation. The results showed that PAI teachers in fostering religious character in PTMT with a hybrid learning model at SMA Antartika Sidoarjo have been able to foster and guide, provide exemplary examples and advice, remind students to behave Islamically in daily life, provide adequate facilities and provide rewards and punishments. for students through the implementation of religious programs, namely congregational prayers, collective prayers, reading and writing the Qur'an, Friday blessing activities, extra religious activities, annual religious activities and the creation of a religious atmosphere at SMA Antarctica Sidoarjo. Several factors that support and inhibit are divided into two factors, namely internal and external. The supporting factors are more dominant on internal factors where the school environment can help optimally to realize the development of students' religious character. While the inhibiting factors are more dominant on external factors, namely the family environment and social environment wherever students are.